Toll-like receptors 7 and 9 regulate the proliferation and differentiation of B cells in systemic lupus erythematosus - Wen, Luyao; Zhang, Bei; Wu, Xinfeng; Liu, Rongzeng; Fan, Hua; Han, Lei; Zhang, Zhibo; Ma, Xin; Chu, Cong-Qiu; Shi, Xiaofei (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the loss of immune tolerance and the production of autoantibodies against nucleic acids and other nuclear antigens (Ags). B lymphocytes play a critical role in the immunopathogenesis of SLE. In patients with SLE, aberrant B-cell activation is controlled by multiple receptors, including intrinsic Toll-like receptors (TLRs), B-cell receptors (BCRs) and cytokine receptors. In recent years, TLRs have been widely studied in the pathogenesis of SLE, particularly TLR7 and TLR9. When endogenous or exogenous nucleic acid ligands are recognized by BCRs and internalized into B cells, they bind with TLR7 or TLR9 to activate related signalling pathways and thus regulate the proliferation and differentiation of B cells. Surprisingly, TLR7 and TLR9 appear to play entirely opposite roles in SLE B cells, and the interaction between them is still poorly understood. In addition, other cells can enhance TLR signalling in B cells of SLE patients by releasing cytokines, accelerating their differentiation into plasma cells. Therefore, delineation of how TLR7 and TLR9 regulate the abnormal activation of B cells in SLE may aid the understanding of the mechanism of SLE and provide directions for TLR-targeted therapies for SLE.